Strategi Digital Marketing Indibiz dalam Meningkatkan Brand Awareness Melalui Konten Instagram Reels - Alexander Nababan; Amiruddin Saleh (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze Indibiz Bogor’s digital marketing strategy in enhancing brand awareness through the use of Instagram Reels, with a specific focus on the role of content creators in planning, producing, and optimizing short-video content. As social media increasingly becomes a primary promotional channel, businesses are required to produce creative and relevant content capable of attracting and engaging audiences effectively. This research employs a qualitative approach, with data collected through observation, interviews, and documentation conducted during October–November 2025. The findings show that content creators play a strategic role in idea development, trend analysis, audience needs identification, and producing visual materials that align with Indibiz’s brand identity. Instagram Reels are proven effective in increasing audience engagement, expanding reach, and strengthening brand perception across digital platforms. However, several challenges persist in the production process, including suboptimal internal coordination, sudden concept revisions, and limited production time. These findings highlight the importance of more structured content planning, improved team communication, and consistent performance evaluation to optimize Indibiz’s digital marketing efforts and maximize their impact on brand awareness.